The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s10519-018-9889-z
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Contributions to Gender Identity and Gender Diversity: Bringing Data to the Table

Abstract: The American Psychological Association defines gender identity as, "A person's deeply-felt, inherent sense of being a boy, a man, or a male; a girl, a woman, or a female; or an alternative gender (e.g., genderqueer, gender nonconforming, gender neutral) that may or may not correspond to a person's sex assigned at birth or to a person's primary or secondary sex characteristics" (American Psychological Association, Am Psychol 70(9):832-864, 2015). Here we review the evidence that gender identity and related soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(86 citation statements)
references
References 91 publications
(82 reference statements)
3
68
0
5
Order By: Relevance
“…Polderman et al (2018) found that heritability estimates across the 11 studies covered a wide range – from around 35% for MZ twin correlations to half that for the DZ twin correlations. Some found similar figures for male- and female-assigned twins.…”
Section: What Is the Evidence For Biological Factors In The Developmementioning
confidence: 99%
See 1 more Smart Citation
“…Polderman et al (2018) found that heritability estimates across the 11 studies covered a wide range – from around 35% for MZ twin correlations to half that for the DZ twin correlations. Some found similar figures for male- and female-assigned twins.…”
Section: What Is the Evidence For Biological Factors In The Developmementioning
confidence: 99%
“…Overall, there appeared to be a negligible role for shared environmental factors and a small potential role for unique environmental factors. The authors of the review concluded that it is sensible to ‘hypothesize that gender identity is a multifactorial complex trait with a heritable polygenic component’ (Polderman 2018, p. 95).…”
Section: What Is the Evidence For Biological Factors In The Developmementioning
confidence: 99%
“…Gender dysphoria (GD) describes a distressing mismatch between one's gender identity and natal sex (American Psychiatric Association, 2013). Not much is known about the origin of GD (Meyer-Bahlburg, 2013), but twin studies show that genetic factors play a substantial role (for a review, see Polderman et al, 2018). Also, prenatal testosterone (T) might have an effect on GD.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies support a genetic component in GD (35,36). In a literature review of twin studies, including unpublished cases from specialized centers, it was possible to show a significantly higher concordance for GD among monozygotic twins than among samesex dizygotic twins (37,38).…”
Section: Etiological Hypothesesmentioning
confidence: 99%